Walt Whitman the song of himself - Loving, Jerome 1941- (Berkeley, Calif. University of California Press, 1999)
A biography of Walt Whitman, the 19th century writer hailed as the father of American poetry. It traces his life as a printer and journalist, before his self-published collection, Leaves of Grass, brought him fame. He was a great promoter, going so far as to write his own book reviews for newspapers. As a poet, he rejected regular meter and rhyme in favor of free verse and blazed the trail as a writer of erotica.
Caresser of life -- Thousand singers, a thousand songs -- Some literary person -- Heart-songs in Brooklyn -- Crescent City sojourn -- Simmering, simmering, simmering -- Beginning of a great career -- New American Bible -- Calamus and the National Calamity -- True love -- Good old cause -- Dalliances of eagles -- Good-bye my fancy.
Includes bibliographical references (pages 487-545) and index.
Keywords: Whitman, Walt -- 1819-1892.; Poets, American -- 19th century -- Biography